2023
DOI: 10.1097/tp.0000000000004701
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Liver Transplantation for Alcohol-associated Liver Diseases in the United States

Abstract: Background. Emerging data suggest disparities exist in liver transplantation (LT) for alcohol-associated liver disease (ALD). As the incidence of ALD increases, we aimed to characterize recent trends in ALD LT frequency and outcomes, including racial and ethnic disparities. Methods. Using United Network for Organ Sharing/Organ Procurement and Transplantation Network data (2015 through 2021), we evaluated LT frequency, waitlist mortality, and graft survival among US adults with ALD (alcohol-associated hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Despite NHB patients showing lower inpatient mortality rates for AH, we noted a lower rate of liver transplants within this demographic. Our study supports previous ndings from various transplant databases (30)(31)(32) and underscores disparities rooted in multifaceted factors. Firstly, there is a noted variation in the severity of alcohol-related liver injury and recovery among racial groups, with NHB individuals potentially experiencing milder AH compared to NHW (26).…”
Section: Discussionsupporting
confidence: 91%
“…Despite NHB patients showing lower inpatient mortality rates for AH, we noted a lower rate of liver transplants within this demographic. Our study supports previous ndings from various transplant databases (30)(31)(32) and underscores disparities rooted in multifaceted factors. Firstly, there is a noted variation in the severity of alcohol-related liver injury and recovery among racial groups, with NHB individuals potentially experiencing milder AH compared to NHW (26).…”
Section: Discussionsupporting
confidence: 91%
“…Transplantation for Alcohol-associated Liver Diseases in the United States Khaled Elsokary, DO, 1 Sonia Samuel, DO, 1 Naoru Koizumi, PhD, 2 and Jorge Ortiz, MD 3 To the Editor, W e read the article entitled "Racial and Ethnic Disparities in Liver Transplantation for Alcoholassociated Liver Diseases in the United States" with great interest. 1 We congratulate the authors for this unique and successful review that identifies the determinants for liver transplant (LT) disparities in patients with alcohol-associated liver disease (ALD).…”
Section: Racial and Ethnic Disparities In Livermentioning
confidence: 99%
“…There was no difference in waitlist or post-LT outcomes by race or ethnicity in alcohol-associated hepatitis (AH) patients, limited by small subgroups. 1 To better understand the demographic impact on listing and survival outcomes among AH LT, we published a retrospective analysis entitled "Demographic inequities exist and influence transplant outcomes in liver transplantation for acute alcohol associated hepatitis." 2 We reviewed the available data using the United Network of Organ Sharing database from 2000 to 2021, specifically 25 981 LT recipients with AAC and 662 recipients with AH, to identify demographic and racial disparities in LT outcomes.…”
Section: 39) Recipients With Alcohol-associated Cirrhosis (Aac)mentioning
confidence: 99%
“…Women also develop cirrhosis with lower amounts of alcohol 19 . A recent study demonstrated that Hispanics, Asians and American Indian/Alaskan Natives had higher hazard ratios (HR) of waitlist deaths in alcohol‐associated cirrhosis when compared to non‐Hispanic Whites 20 . In the United States, young age, female gender and Hispanic race are independently associated with both the burden of ALD and the occurrence of ACLF 21 .…”
Section: Natural History Diagnosis and Healthcare Disparities Of Alco...mentioning
confidence: 99%